Airborne biological hazards and urban transport infrastructure: current challenges and future directions - Nasir, Zaheer A.; Campos, L. C.; Christie, N.; Colbeck, I. (Springer, 2016)
Exposure to airborne biological hazards in an ever expanding urban transport infrastructure and highly diverse mobile population is of growing concern, in terms of both public health and biosecurity. The existing policies and practices on design, construction and operation of these infrastructures may have severe implications for airborne disease transmission, particularly, in the event of a pandemic or intentional release of biological of agents. This paper reviews existing knowledge on airborne disease transmission in different modes of transport, highlights the factors enhancing the vulnerability of transport infrastructures to airborne disease transmission, discusses the potential protection measures and identifies the research gaps in order to build a bioresilient transport infrastructure. The unification of security and public health research, inclusion of public health security concepts at the design and planning phase, and a holistic system approach involving all the stakeholders over the life cycle of transport infrastructure hold the key to mitigate the challenges posed by biological hazards in the twenty-first century transport infrastructure
Keywords: Biological hazards; Transport; Vulnerability; Protection measures